Kentucky's Age of Wood - Clarke, Kenneth, 1917-; Kohn, Ira (Book collections on Project MUSE., 2009)
The old tools and wooden objects illustrated in this book are homely reminders of a time when the majestic forests of the frontier were the source not only of the pioneer's house, barn, and fences, but of his children's toys, his wife's egg basket, and a hundred other necessities and pleasures. More than fifty delicate line drawings by Ira Kohn and the clear, nontechnical discussion by Kenneth Clarke of the making and uses of these humble objects -- many of them unfamiliar to the eyes of the current generation of Kentuckians -- give the reader new insight into the life of the pioneer.